2014
DOI: 10.1186/1472-6882-14-202
|View full text |Cite
|
Sign up to set email alerts
|

Reversal by aqueous extracts of Cistanche tubulosa from behavioral deficits in Alzheimer’s disease-like rat model: relevance for amyloid deposition and central neurotransmitter function

Abstract: BackgroundCistanche tubulosa (Schenk) R. Wight (CT) is commonly used to treat forgetfulness by traditional Chinese physicians. This study presents the ameliorating effects of CT extract which was quantified with three phenylpropanoid glycosides in Alzheimer’s disease (AD)-like rat model.MethodsAmyloid β peptide 1-42 (Aβ 1-42) intracisternally infused to rats by osmotic pump (Alzet 2002) was used as an AD-like rat model. The major pathological makers were measured including Aβ 1-42 immunohistochemical stain, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 25 publications
5
89
0
Order By: Relevance
“…Verbascoside, one of the main active phenylpropanoid glycoside from M. tomentosa leaves, was reported to reverse memory impairment induced by a combination of D-gal and AlCl 3 in a senescent mouse model [19]. Isoverbascoside, another phenylpropanoid glycoside from M. tomentosa leaves, ameliorated cognitive deficits in AD-like rat model induced by administration of Aβ1–42 through blocking of amyloid deposition, reversing cholinergic and hippocampal dopaminergic neuronal function [20]. Oleanolic acid, a triterpene identified in the stem bark of M. tomentosa , exhibited neuroprotective effects and improved Aβ-induced memory deficits in mice [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Verbascoside, one of the main active phenylpropanoid glycoside from M. tomentosa leaves, was reported to reverse memory impairment induced by a combination of D-gal and AlCl 3 in a senescent mouse model [19]. Isoverbascoside, another phenylpropanoid glycoside from M. tomentosa leaves, ameliorated cognitive deficits in AD-like rat model induced by administration of Aβ1–42 through blocking of amyloid deposition, reversing cholinergic and hippocampal dopaminergic neuronal function [20]. Oleanolic acid, a triterpene identified in the stem bark of M. tomentosa , exhibited neuroprotective effects and improved Aβ-induced memory deficits in mice [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it has been reported that ginsenosides can restore metabolite imbalance in AD mice [24]. Wu et al [25] suggested that Cistanche tubulosa extract could ameliorate the cognitive dysfunction in AD-like rat model. Moreover, α -asarone can inhibit proinflammatory cytokines and microglial activation in the hippocampus and ameliorate memory deficits [26].…”
Section: Introductionmentioning
confidence: 99%
“…Echinacoside (ECH) is a major bioactive component found in the medicinal herb C. tubulosa . Studies have shown the therapeutic effects of glycosides of Cistanche and ECH, verbascoside (VER) and icariin (ICA) on Alzheimer’s disease (AD), PD and other vascular dementia patients (Urano and Tohda, 2010; Wang et al, 2013; Wu et al, 2014). Wu et al (2014) suggested that C. tubulosa extracts that contained enough ECH and acteoside ameliorated the cognitive dysfunction caused by Aβ-42 via blocking amyloid deposition, and reversing cholinergic and hippocampal dopaminergic neuronal function.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the therapeutic effects of glycosides of Cistanche and ECH, verbascoside (VER) and icariin (ICA) on Alzheimer’s disease (AD), PD and other vascular dementia patients (Urano and Tohda, 2010; Wang et al, 2013; Wu et al, 2014). Wu et al (2014) suggested that C. tubulosa extracts that contained enough ECH and acteoside ameliorated the cognitive dysfunction caused by Aβ-42 via blocking amyloid deposition, and reversing cholinergic and hippocampal dopaminergic neuronal function. Tao et al (2015) found that phenylethanoid glycosides from C. tubulosa (Ph Gs-Ct) prevented high altitude cerebral edema by decreasing the protein and mRNA expression of AQP4 in the brain tissue of rat models.…”
Section: Introductionmentioning
confidence: 99%